2013
DOI: 10.1182/blood.v122.21.2238.2238
|View full text |Cite
|
Sign up to set email alerts
|

Extrahepatic Iron Deposition In Chronically Transfused Children With Sickle Cell Anemia – Baseline Findings From The Twitch Trial

Abstract: Introduction Chronic transfusion therapy is the standard of care for children with sickle cell anemia (SCA) and abnormal transcranial Doppler velocities. Although effective, monthly transfusions are costly, inconvenient, and produce iron overload in the liver and extrahepatic organs. The TWiTCH study (ClinicalTrials.gov NCT01425307) is a randomized clinical trial to determine whether hydroxyurea therapy leads to comparable time averaged TCD velocities as conventional transfusion therapy, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…In the previous version of this Cochrane Review (Wang 2013) the review authors identified a total of 89 references: 80 references related to three included trials (STOP 1998; STOP 2 2005; SWiTCH 2012) and nine to three ongoing trials (SCATE 2015; SIT 2014; TWiTCH 2016).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the previous version of this Cochrane Review (Wang 2013) the review authors identified a total of 89 references: 80 references related to three included trials (STOP 1998; STOP 2 2005; SWiTCH 2012) and nine to three ongoing trials (SCATE 2015; SIT 2014; TWiTCH 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Two review authors (LE, PF) excluded 777 records on the basis of the abstract, and two authors (LE, PF) reviewed 83 full text articles for relevance. We identified two completed trials within 22 publications which were classified as ongoing trials in the previous version of this review (SIT 2014,TWiTCH 2016). We identified 60 citations related to previously included trials (STOP 1998; STOP 2 2005, SWiTCH 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations